Autoimmune Enteropathy in Children: Review of Literature and Own Supervision - M.P. Limarenko; N.G. Logvinenko; A.P. Mayorenko (Zaslavsky O.Yu., 2013)
The article deals with rare disease in children - autoimmune enteropathy. The basis of the disease is persistent protein-losing diarrhea, associated with production of autoantibodies, - a sign of an active autoimmune T-cell inflammation. Histomorphologically, the disease is characterized by atrophy of the villi and massive mononuclear infiltration of lamina propria of the small intestine. The article presents a review of literature and our own observations of autoimmune enteropathy in infant. Disease in a child ended fatally, as initially it had a poor prognosis: early onset, persistent diarrhea, renal involvement (nephrotic syndrome), associated defeat of small and large intestines.